Assessment of flood risk under Polder-Type flood control measure using improved projection pursuit model - Li Gao; Yuqin Gao; Yunping Liu; Ming Wu (Ecological Indicators)
Floods are the most common natural disaster worldwide and significantly impact human society and ecosystems. Therefore, research on flood risk assessment and zoning is crucial. Constructing polders in river deltas changes flood formation mechanisms and processes, impacting flood risk. This study proposes an integrated flood risk assessment model combining index-based evaluation, the best worst method, the projection pursuit model optimized by CPSGA, game theory, and the hydrological-hydrodynamic model, which was implemented in the Qinhuai River Basin to assess and zoning the flood risk. The results show that the integrated model allows an excellent flood risk assessment under different scenarios. Spatially, the high and highest-risk areas are mainly distributed in the urban areas, concentrated in densely populated and economically developed areas. Compared with the natural stream (without the PFCM), the high and highest risk areas decreased 0.06, 0.04, and 0.58 km2 for 50 %, 30 %, and 3 % frequency flood scales, respectively. The proposed integrated model characterizes the spatial distribution of flood risk, understands the impact of polders on flood risk, and provides a reference for implementing integrated and efficient flood risk management.